Pengembangan Aplikasi Augmented Reality Berbasis Android dalam Pembelajaran Geometri Bangun Ruang di Sekolah Dasar - Putri Shabira Pratiwi; Shinta Puspasari; Mustafa Ramadhan (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to develop an Augmented Reality (AR) application for Android devices to support the teaching of three-dimensional geometry in primary education. The development process employed the Multimedia Development Life Cycle (MDLC) model, which consists of six stages: concept, design, material gathering, assembly, testing, and distribution. The application is designed to display three-dimensional representations of basic geometric figures such as cubes, cuboids, prisms, pyramids, cylinders, cones, and spheres. In addition to visual models, the application also provides related mathematical equations and explanatory commentary to strengthen students’ conceptual understanding. The testing phase demonstrated that the AR application is capable of presenting 3D objects with clarity and stability when viewed from a distance of 10–30 cm and within an angle range of 45° to 135°. These conditions ensure that the objects remain easily recognizable and interactive in classroom learning environments. User feedback from both teachers and students highlighted the engaging nature of the application, particularly in fostering motivation, improving visualization skills, and encouraging interactive learning experiences. Overall, the findings suggest that this AR-based application can serve as an effective educational tool for primary school students, bridging the gap between abstract geometry concepts and practical visualization. By integrating modern technology into mathematics instruction, the application has the potential to enhance both comprehension and interest in learning geometry while supporting innovative digital learning practices in the classroom.